A rare complication of prosthetic mesh repair of a ventral incisional hernia: erosion and enterocutaneous fistula formation - M., Sridhar Reddy; M., Naresh; Rath, Alok; M. A., Saleem (International Surgery Journal, 2018)
Recurrence of hernia has significantly reduced with mesh repair. But mesh is a foreign material which has its own complications like haematoma, infection, sinus formation, mesh migration and erosion. Mesh migration and erosion although rare, is a challenging complication which requires surgical intervention. There are very few such mesh related complications reported in the literature. Authors report a case of mesh erosion resulting in chronic infection and formation of enterocutaneous fistula following incisional hernia repair 5 years after surgery. In this case small bowel segment containing mesh was resected and primary anastomosis was done. Migration of mesh also depends on the nature of mesh (biomaterial) and type of fixation. Although many techniques of hernia repair have been described (open or laparoscopic) care must be taken to fix the mesh to abdominal wall for prevention of delayed complications. Different techniques of repair, types of meshes have been discussed to prevent such complications.